METHODOLOGY FOR MEASURING TRAFFIC SIGNS RETROREFLECTION - Shcukanec, Andjelko; Babic, Dario; Sokol, Hrvoje (European Scientific Journal, ESJ, 2014)
Increase of traffic congestion and speed, as a result of the development of modern society require high-quality solutions in the field of traffic signalization. Modern traffic signalization needs to enable right decision making in order to secure a safe and optimal traffic flow. One of the key elements of traffic signalization is timely detection which, followed by reading and understanding its meaning, allows drivers to make proper response in accordance with the requirements of the situation. Quality solutions in the field of traffic signalization, especially traffic sings, can be achieved with relatively small investments through application of modern technologies and continuous inspection and maintenance. Important element of traffic signs maintenance is their retroreflectivity measurement. In order to ensure a satisfying level of retroreflection, continuous measurements in accordance with prescribed standards and technical requirements, should be carried out. The aim of this paper is to analyze the importance of traffic sings retroreflection measurement as a part of standard maintenance program in order to increase road safety.